O Brasil é o país do futuro : rock e contestação nas canções de Renato Russo (1978/1990) - Franco, Deivid Fernando (2015)
The research starts from the premise that the Rock music of the 1980s served as a cultural practice, as a critical tool, nonconformity and reflection on the political, social and economic situation of Brazil. The work takes as a research subject the Rock music of that time, considering the many rock bands that emerged in the period, but restricting analysis to the songs composed by Renato Russo, a musician who has appeared both in solo and in the bands Aborto Eletrico and Legião Urbana. So, the analysis was performed on some compositions focusing on the speech diffused by the musician, in order to realize his political positioning. The period which is being covered in the research takes as its starting point the year 1978, when the first compositions from the musician aroused, until 1990, when was released the album called "As Quarto Estações". Our sources are the songs and speech found in Renato Russo s compositions and the interviews he granted to the music press